2018
DOI: 10.1002/jcb.28146
|View full text |Cite
|
Sign up to set email alerts
|

Study of p16 promoter methylation in Egyptian colorectal cancer patients

Abstract: Many tumor‐suppressor genes contain CpG islands in their promoter regions which raised the necessity of investigating the role of methylation in silencing these genes. We examined p16 methylation as a potential biomarker in the peripheral blood of colorectal cancer (CRC) patients. Using methylation‐specific polymerase chain reaction method, the methylation status of p16 was investigated in the tumor tissue and blood of 65 CRC patients and blood samples from 70 healthy control individuals. Also, the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As previously mentioned, several studies evaluated mSEPT9 within diagnostic panels or in combination with other markers. Three studies in particular [ 66 , 151 , 153 ] showed the sensitivity of mSEPT9 to detect CRC increased when combined with more established markers such as FIT and CEA. The results from our review show a slightly higher sensitivity for mSEPT9 in comparison to a recent meta-analysis of 19 studies [ 165 ] though it should be noted the analysis from that review included a mixture of study designs and focused on high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, several studies evaluated mSEPT9 within diagnostic panels or in combination with other markers. Three studies in particular [ 66 , 151 , 153 ] showed the sensitivity of mSEPT9 to detect CRC increased when combined with more established markers such as FIT and CEA. The results from our review show a slightly higher sensitivity for mSEPT9 in comparison to a recent meta-analysis of 19 studies [ 165 ] though it should be noted the analysis from that review included a mixture of study designs and focused on high-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 7212 publications were queried based on our search strategy at first, and 79 eligible articles published from 2008 to 2022 were incorporated into our meta-analysis after examination of the abstract and comprehension of the full text ( Table S1 ). All included studies consisted of quantitative analysis of ctDNA concentration ( n = 11) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] and qualitative analysis of tumor-specific gene methylation in ctDNA ( n = 67) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , ...…”
Section: Resultsmentioning
confidence: 99%
“…It functions by inhibiting the growth of tumor-killing cells (Muss et al, 2020). Several studies have indicated that hypermethylation of the p16 gene is strongly associated with poor prognosis in patients diagnosed with colorectal cancer (Karam et al, 2019), liver cancer (Wong et al, 1999), and lung cancer (Peng et al, 2023). Another gene involved in cancer development is glutathione S-transferase 1 (GSTP1).…”
Section: Line-1mentioning
confidence: 99%